Muhibbah frozen unified Tawhidic balancing growth, workforce care, and product integrity - Mhd Sarif, Suhaimi; Muhamad Ibrahim, Najhan; Abdul Razak, Arbaiah; Abdul Sabian, Nur Arfifah; Abdul Wahid, Mohamad Fikri (IIUM Press, 2026)
This case examines Muhibbah Frozen, a Malaysian small food manufacturing enterprise navigating growth decisions under capacity, financial, and ethical constraints. Faced with competing purchase orders, the founder, Ismail Muhibbah, must balance expansion opportunities against workforce well-being, product integrity, and long-standing community trust. Drawing on lived entrepreneurial experience, industry advice, government training, and Tawhidic epistemology, the case highlights how strategic decisions are moral acts shaped by intention, stewardship, and accountability. The case invites discussion on selective growth, stakeholder balance, and how faith-informed reasoning can guide sustainable enterprise development toward ummatic excellence rather than rapid scale alone